The Implementation of Adiwiyata Program to Improve Character of Students Concern in Maintaining the School Environment at SD Negeri 101768 Tembung Academic Year 2022/2023 - Adinda Istiqomah; Faiza Arsila; Nanda Syakira Lubis; Roudhotul Jannah Hasibuan; Laurensia M. Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to increase students' concern for protecting the school environment at SD Negeri 101768 Tembung. Then, describe the formation of environmental care behavior and the obstacles experienced by schools and how to overcome them. This research is a classroom action research (CAR), namely planning, action, observation, reflection. The approach used is qualitative with descriptive method. The obstacles faced by the school in shaping students' environmental care behavior are student turnover every new school year, socio-economic conditions, educator concern. Solutions that can be done are, for example, socializing new programs to participants and students, monitoring and always reminding student behavior, involving teachers in workshops or seminars on environmental themes.